Mr. Lion Dresses Up! - Teckentrup, Britta; Hardenberg, Wendeline A. (California: Twirl Books, 2020)
How exciting! Mr. Lion has been invited to a party. But, uh-oh, what will he wear? His mischievous friend Monkey offers lots of suggestions. Perhaps Mr. Lion can wear a handsome suit . . . striped pajamas . . . a superhero costume . . . or maybe an evening gown? Renowned author and illustrator Britta Teckentrup's playful dress-up book with a die-cut on every spread takes readers on a fanciful journey through Mr. Lion's many wardrobe changes. Children will laugh out loud at the increasingly crazy outfits and will join Mr. Lion in learning that it's not about what you wear, but about always being yourself.
new kids book 2025 winter.
Keywords: Mr Lion dresses up; Clothing and dress; Board books; Humorous fiction